The effects of varying dietary fat on performance and metabolism in trained male and female runners - Horvath, P. J.; Eagen, C. K.; Fisher, N. M.; Leddy, J. J.; Pendergast, D. R. (Journal of the American College of Nutrition, 2000)
OBJECTIVES: Low dietary fat intake has become the diet of choice for many athletes. Recent studies in animals and humans suggest that a high fat diet may increase VO2max and endurance. We studied the effects of a low, medium and high fat diet on performance and metabolism in runners. METHODS: Twelve male and 13 female runners (42 miles/week) ate diets of 16% and 31% fat for four weeks. Six males and six females increased their fat intakes to 44%. All diets were designed to be isocaloric. Endurance and VO2max were tested at the end of each diet. Plasma levels of lactate, pyruvate, glucose, glycerol, and triglycerides were measured before and after the VO2max and endurance runs. Free fatty acids were measured during the VO2max and endurance runs. RESULTS: Runners on the low fat diet ate 19% fewer calories than on the medium or high fat diets. Body weight, percent body fat (males=71 kg and 16%; females=57 kg and 19%), VO2max and anaerobic power were not affected by the level of dietary fat. Endurance time increased from the low fat to medium fat diet by 14%. No differences were seen in plasma lactate, glucose, glycerol, triglycerides and fatty acids when comparing the low versus the medium fat diet. Subjects who increased dietary fat to 44% had higher plasma pyruvate (46%) and lower lactate levels (39%) after the endurance run. CONCLUSION: These results suggest that runners on a low fat diet consume fewer calories and have reduced endurance performance than on a medium or high fat diet. A high fat diet, providing sufficient total calories, does not compromise anaerobic power.